A modified high step-up non-isolated DC-DC converter for PV application - Saravanan, Subramani; Babu, Neelakandan Ramesh (Journal of applied research and technology, 2017)
A non-isolated high voltage gain DC-DC converter has been presented in this paper. The boost, SEPIC and modified SEPIC converters were analyzed and their performance was compared with the proposed converter. The proposed converter has been designed for the input voltage of 15V and an output voltage of 150V with 100W output power. The efficiency of the converter obtained was 92.5%, which is higher than that of the other converter models which were analyzed. Also, the proposed converter utilizes reduced input current and shows low switching voltage stress. The time response analysis conveys that the proposed converter settles to the steady state voltage and current faster than the other compared converters.